Induction of trapping rings and assessment of predacity of Dactylaria brochopaga against some plant parasitic nematodes - P. BANDYOPADHYAY, K.P.SINGH and (Indian Phytopathology, 2002)
Dactylaria brochopaga Drechsler is a widely distributed fungus, which produces trapping rings directly on the spores in presence of nematodes. Induction of trapping rings of this fungus was studied by suspending spores with varying numbers of a plant parasitic nematodes in 0.5 ml sterile distiUed water in cavity block. AU the six species of the plant parasitic nematodes induced traps directly on the spores of this fungus. The maximum ring induction was observed in presence of second stage juveniles of Heterodera cajani followed by second stage juveniles of Meloidogyne incognita, Tylenchorhynchus brassicae, Helicotylenchus dihystera, Hoplolaimus indicus and Xiphinema basiri. The maximum ringing (pre capturing), trapping and killing was recorded for second stage juveniles of M.incognita followed by T.brassicae and H.dihystera. Second stage juveniles of H. cajani recorded lowest percentage of ringing and killing by this fungus. Hoplolaimus indicus and X. basiri were neither captured nor killed by this fungus. The inflation of ring cells did not occur immediately after ringing. The time between ringing and inflation varied in different nematodes as well as in the same species. Clear hyphae were observed in the invaded nematode body after the content of nematode body was consumed. External growth of hyphae occurred only from the inflated cells of the constricting ring, that further developed several rings. Higher number of rings were observed in mycelium developed from bigger nematodes.